PEREMPUAN YANG MEMBATALKAN SHALAT - Syaikhudin, Syaikhudin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
The hadith that states that â€œWomen, donkeys and dogs break prayersâ€ is aÂ controversial one. Because to many feminine thinkers, it subordinates womenÂ to the same level as those two other furry animals, and thus contradictory to universal values of humanity and equality and should therefore be rejected. What is also interesting to note is that this was also questioned in the time of the prophet by Aisyah, who claimed that this tradition insulted women and likened them to bad beasts. Such critical objection is controversial and vital, since Aisyah was one of the people close to the prophet and herself a prominent historical actor of the time.